2013
DOI: 10.1371/journal.pone.0077068
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Suppressive Function of miR-139-5p in Esophageal Squamous Cell Carcinoma

Abstract: Recent studies have demonstrated the possible function of miR-139-5p in tumorigenesis. However, the exact mechanism of miR-139-5p in cancer remains unclear. In this study, the association of miR-139-5p expression with esophageal squamous cell carcinoma (ESCC) was evaluated in 106 pairs of esophageal cancer and adjacent non-cancerous tissue from ESCC patients. The tumor suppressive features of miR-139-5p were measured by evaluating cell proliferation and cell cycle state, migratory activity and invasion capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 30 publications
5
52
0
Order By: Relevance
“…However, miR-139-5p was not selected for validation. In other studies, it was consistently downregulated in ccRCC metastatic samples and oesophageal squamous cell carcinoma tissues obtained from patients with lymph node metastasis (Wu et al , 2012; Liu et al , 2013). miR-139-5p was also found to be associated with ccRCC survival in some studies but not all (Osanto et al , 2012; Wu et al , 2012).…”
Section: Discussionmentioning
confidence: 67%
“…However, miR-139-5p was not selected for validation. In other studies, it was consistently downregulated in ccRCC metastatic samples and oesophageal squamous cell carcinoma tissues obtained from patients with lymph node metastasis (Wu et al , 2012; Liu et al , 2013). miR-139-5p was also found to be associated with ccRCC survival in some studies but not all (Osanto et al , 2012; Wu et al , 2012).…”
Section: Discussionmentioning
confidence: 67%
“…An increasing number of studies focusing on miR‐139‐5p have been published in recent years, which indicate that miR‐139‐5p is closely correlated to human cancers by affecting various biological functions . Our previous studies provided evidence that miR‐139‐5p was down‐regulated in human CRC samples, and is associated with tumor staging .…”
Section: Discussionmentioning
confidence: 89%
“… also clarified the function of miR‐139‐5p as a tumor inhibitor by inducing apoptosis and causing cell cycle arrest in G0/G1 phase through targeting NOTCH1. Other studies have determined the effects of miR‐139‐5p on proliferation and apoptosis in other types of cancer . In the present study, we also evaluated the influence of miR‐139‐5p depletion on proliferation and apoptosis in an AOM/DSS mouse model.…”
Section: Discussionmentioning
confidence: 91%
“…Shen et al (22) demonstrated that miR-139 expression was also downregulated in colorectal cancer tissues compared with that in adjacent non-tumorous tissues, and decreased miR-139 expression has also been associated with colorectal cancer progression and metastasis. Furthermore, in a study by Liu et al (23), miR-139 expression was demonstrated to be reduced in esophageal squamous cell carcinoma tissues, and this reduction was associated with lymph node metastasis. These findings indicate that increasing miR-139 expression may be useful in the prevention of cancer progression.…”
Section: Discussionmentioning
confidence: 93%